Identifikasi Nematoda Tanah Pada Perkebunan Sawi (Brassica juncea L.) di Kelurahan Landasan Ulin Utara, Banjarbaru, Kalimantan Selatan: Identification of Soil Nematodes in Mustard Plantation (Brassica juncea L.) in Landasan Ulin Utara Village, Banjarbaru, South Kalimantan - Oktaviani, Yusinta; Gafur, Abdul (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2020)
Nematodes are microscopic worms belonging to the soil biota with high species diversity. Nematodes have different compositions in different types of soil and areas. This research is conduct to determine the presence and genus of soil nematodes found in mustard plantations in Landasan Ulin Utara Village, Banjarbaru, South Kalimantan. Soil samples are taken from community vegetable plantations with a depth of 0-20 cm around the mustard plant rhizosphere located in ??Jalan Kurnia and Jalan Sukamara, Landasan Ulin Utara Village, Banjarbaru. Extraction to separate nematodes from soil using the Whitehead & Hemming method (1965) and nematode fixation using the Seinhorst method (1959). Furthermore, the permanent nematode preparations were made for the identification stage by morphological observations and morphometric measurements. The identification results showed that the genera of nematodes found in the study site's soil samples were Iotonchus, Crustorhabditis, Ironus, and Xiphinema.